ʺDesign and technological activities of education applicants as a means of forming key competencesʺ - Hahatik, N. (Problems of Engineer-Pedagogical Education, 2024)
The article is devoted to one of the important problems in professional and technical education, the formation of design and technological competence through the results of mastering design and technological activities. The process of forming the project-based learning activities for students in the educational process involves the diagnostic assessment of both the external and internal educational products of students. External educational products are manifested in the form of a manufactured product, internal - in the form of an individual level of formed professional competences, which collectively are a manifestation of general competence. In the personally oriented process of professional training, internal educational products are prioritized over external ones. The article is devoted to an experiment that confirmed the effectiveness of the method of forming the design and technological competence of students of vocational and technical institutions in the construction field in the educational process. The specified activity equips students of vocational and technical institutions of construction with a universal tool for learning and transforming the surrounding reality, and also forms the ability and readiness to solve real problems, effective partnership interaction, objective self-evaluation of the results of their own activities, which ensures the continuous growth of their educational and cultural level. The article does not reveal all aspects of the problem, all possibilities of the educational process regarding the formation of design and technological competence. The arguments presented in the article encourage further research on the topic, in particular, there is a need for a thorough study of the following issues: studying the idea of a portfolio as a basis for objective assessment of the level of development of design and technological competence of students of vocational and technical institutions in the construction field; identification of socially and professionally important personality qualities of vocational and technical institutions for adequate self-determination regarding the educational and professional path. The formation of project-technological competence is one of the purposeful activities of the educational process of the vocational and technical education institution in order to ensure the quality training of qualified workers, with the aim of increasing the effectiveness of their educational and educational activities. It contributes to the personal development of the recipient and increases his key competencies. The article states that the application of project-technological competence in a vocational and technical education institution contributes to the involvement of education seekers in active cooperation, developing in them a positive attitude towards the educational process and interest in obtaining positive results. The article proves that the formation of design and technological competence will contribute to the development of education, upbringing, creative development and the expansion of their professional outlook.